Enhancement of the DOA detection performance through optimization of the steering matrix of the array - Xiao, Guoyao; Liao, Guisheng (Frontiers in Physics, 2022)
Direction Of Arrival (DOA) detection technology is a key technology in the field of in remote sensing, radar, wireless communication. In this study, we elaborate on an enhanced method to detect the direction of arrival of signals. In the developed scheme, we mainly focus on solving the steering matrix of the array which contains all the information of the signals. The iterative relation between the steering matrix and the signal vector is first established on the basis of the equation of the array output. Then, to get a more accurate of steering matrix, we construct a cost function that aims to minimize some signal subspace error. In the optimization process of the developed scheme, we also set a constraint for the steering matrix which can effectively eliminate convergence on local optimum and also reduce the number of iterations. Subsequently, the steering matrix of the array can be recovered faithfully. Finally, the DOA can be solved from the steering matrix. Explicit analysis and derivation of the proposed scheme are presented.